The Impact of Electronic Government Procurement (EGP) on Financial Reporting: A Case of Audit House - Caleb Bright Ainomujuni (Uganda Christian University, 2024)
This study explores the transformative impact of electronic government procurement (e-GP) on financial reporting within public sector auditing, focusing on a case study of the Audit House. With the rise of digital solutions in governance, e-GP systems have emerged as a pivotal tool in enhancing transparency, accountability, and efficiency in procurement processes. This research, employing a qualitative approach, delves into how these technological advancements have reshaped financial reporting practices. Through in-depth interviews with 18 out of 25 targeted respondents, insights were gathered on the perceived changes in the accuracy, timeliness, and reliability of financial reports post-e-GP implementation. The findings reveal a nuanced interplay between technology and traditional auditing practices, highlighting both the benefits and challenges faced by auditors in adapting to this digital shift. Ultimately, this study contributes to the growing discourse on e-GP’s role in fostering more robust financial reporting mechanisms in the public sector, offering valuable lessons for policymakers and audit professionals alike.